2009
DOI: 10.1021/jf8030925
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Extraction of Phenolic Antioxidants from Peanut Skins Using Response Surface Methodology

Abstract: Peanut skins are a byproduct of peanut blanching operations and contain high levels of phenolic antioxidants. The effect of solvent type (methanol MeOH, ethanol EtOH, and water), concentration (0, 30, 60, 90%), temperature (30, 45, 60 degrees C), and time (10, 20, 30 min) on total phenolic content (TPC), oxygen radical absorbance capacity (ORAC) level, and resveratrol content of peanut skins was investigated. Response surface methodology was used to estimate the optimum extraction conditions for each solvent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 37 publications
4
74
0
4
Order By: Relevance
“…Extraction of these compounds has been studied with various extraction solvents. Using the Folin-Ciocalteu method, TPC of peanut skins extracted with pure ethanol has been reported as 118 mg/g [11]. Under optimized conditions, similar levels were found with an ethanol-water mixture [9].…”
Section: Total Phenolics and Antioxidant Activitymentioning
confidence: 75%
See 1 more Smart Citation
“…Extraction of these compounds has been studied with various extraction solvents. Using the Folin-Ciocalteu method, TPC of peanut skins extracted with pure ethanol has been reported as 118 mg/g [11]. Under optimized conditions, similar levels were found with an ethanol-water mixture [9].…”
Section: Total Phenolics and Antioxidant Activitymentioning
confidence: 75%
“…Of these materials, peanut skins are most commonly used as low cost fillers in animal feed but are known to have an astringent taste and anti-nutrient properties [7]. The antioxidant activity of peanut skins has been reported [8][9][10][11], but there are no reports in the scientific literature regarding the relationship between antioxidants, their activity, and anti-inflammatory properties of peanut skins.…”
Section: Introductionmentioning
confidence: 99%
“…RSM was used to evaluate the effects of multiple factors and their interactions on one or more response variables, and to find the optimum combination of factor levels (Ballard et al, 2009 …”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies concluded that higher temperatures damage phenolic compounds and cause a loss in the yield (Sun et al 2011; Fig. 2 Response surface plots for total phenolic (TP), total anthocyanin (TA), cyanidin-3-glucosylrutinoside (Cy-3GR), neochlorogenic acid (NcA) and catechin (Cat) in function of ethanol concentration, temperature and solvent ratio Ballard et al 2009;Cacace and Mazza 2003). Silva et al (2007) and Pinelo et al (2005) kept the temperature degrees at certain levels by considering higher temperature may cause degradation of phenolics.…”
Section: Fitting the Modelsmentioning
confidence: 99%